Synthesis and characterization of apatite silicated powders with wet precipitation method - Labjar Houda; Chaair Hassan (E3S Web of Conferences, 2021)
The synthesis of apatite silicated Ca10(PO4)6-x(SiO4)x(OH)2-x (SiHA) with 0≤x≤2 was investigated using a wet precipitation method followed by heat treatment using calcium carbonate CaCO3 and phosphoric acid H3PO4 and silicon tetraacetate SiC8H20O4 (TEOS) in medium of water ethanol, with three different silicate concentrations. After drying, the samples are ground and then characterized by different analytical techniques like X-ray Diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning electron Microscopy (SEM) and chemical analysis.